AVAILABILITY, ACCESS AND USE OF ELECTRONIC INFORMATION RESOURCES IN TERTIARY INSTITUTIONS OF ANAMBRA STATE, NIGERIA - Obiajulu Ibenegbu, Queendaline; U. Ugwu, Theresa; Onyinye Muojekwu, Helen; Ijeamasi Enebech i, Regina; Regina Ugochi, Chukwunta; Blessing Ijeoma, Okafor; Anigbogu, Grace; Danjuma Gokum4, Katkukah; Nanfwang Dohol, Auta; Musa Rike, Juliana; Goyit, Iliya; Easter C, Adepoju; et al. (Cuestiones de Fisioterapia, 2023)
This study is on the availability, access, and use of electronic information resources in tertiary institutions in Anambra State, Nigeria. The study employed a descriptive survey design. Two hundred and twenty-five undergraduate students and seventy-nine lecturers from tertiary institutions in Anambra State were used for the study. Observational Checklist and Questionnaire on Electronic Information Resources (EIR) were the instruments used to collect data for the study. Five research questions were answered and three hypotheses were tested. The data were analyzed using frequency percent, mean and standard deviation and Independent Samples t-test. The result showed that Most EIR facilities are not available in most tertiary institutions in Anambra state; the EIRs are not thoroughly accessible by lecturers and students in tertiary institutions of Anambra state; there was no significant difference in mean rating scores for lecturers (M=2.49, SD=.73) and students (M=2.51, SD=.81), t(.115) = 302, p = .909 two-tailed on the use of EIR in tertiary institutions; there was no significant difference in mean rating scores for lecturers (M=3.19, SD=.73) and students (M=3.28, SD=.64), t(.925) = 302, p = .356 two-tailed on the reasons for using Electronic Information Resources in tertiary institutions and there was no significant difference in mean rating scores for lecturers (M=3.28, SD=.68) and students (M=3.38, SD=.61), t(-1.27) = 302, p = .205 two-tailed on the barriers to effective use of electronic information resources. Based on the findings and implications, it was recommended that schools should make extra efforts to source for the fund from both the government, cooperate organizations and alumni to adequately equip schools with ICT facilities that will help for effective use of EIR. It was suggested that the present study could be replicated in other tertiary institutions in Nigeria other than the ones used for this study.